Determinants of gross domestic product growth in Malaysia / Muhammad Amin Shah Shahrin - Shah Shahrin, Muhammad Amin (Universiti Teknologi Mara Perlis, 2020)
Gross Domestic Product (GDP) growth has always been treated as current issue that studied by many researchers. This study is to investigates the relationship between Gross Domestic Product (GDP) growth and the factors such as Foreign Direct Investment (FDI), Inflation (INF), Gross Fixed Capital Formation (CF), and Interest Rate (IR) in Malaysia. Annual time series data for the 1985 to 2018 periods. This study used E-View includes, Augmented Dickey Fuller test and Philips Perron test are used for the analysis. The results identify that gross fixed capital formation (CF) have positive impact on GDP growth in Malaysia. However, FDI and INF have negative significant relationship with GDP growth. The only variable that negative insignificant to GDP growth is interest rate. Based on the result, it is suggested by maintaining the stability on gross fixed capital formation (CF) will lead to rising in GDP.